Avoiding the dry season: dispersal time and syndrome mediate seed dormancy in grasses in Neotropical savanna and wet grasslands. (28th April 2017) - Ramos, Desirée M.; Diniz, Pedro; Ooi, Mark K.J.; Borghetti, Fabian; Valls, José F.M.
Abstract: Question: In seasonal rainfall systems, seed dormancy is a strategy to avoid germination and seedling emergence in the dry season. Grass species in Brazilian savannas ( Cerrado ) show variation in seed dispersal timing and mechanisms, and occur in different habitat types (distinguished by soil moisture) within a seasonal rainfall environment. However, it is unknown whether dormancy has evolved in these systems as a dominant way in which germination is deferred, or how it correlates with other key traits such as dispersal, where known trade‐offs exist for avoiding competition. We asked whether seed germination and dormancy vary with dispersal and abiotic factors in savanna systems. Specifically, we assessed dormancy by comparing seeds: (1) from species living in habitats with contrasting soil moisture during the dry season (open savannas vs wet grasslands); (2) dispersed at different times (early in the wet season, late in the wet season and in the dry season); and (3) showing alternate dispersal syndromes (barochoric vs anemochoric). Location: Open savannas and wet grasslands in central Brazil. Methods: We collected seeds of 29 grass species and tested viability and dormancy using germination trials with fresh seeds, which was then repeated after dry storage for 3, 6, 9 and 12 mo. GLMM were used to test whether the degree of dormancy was dependent on habitat type, seed dispersal time and seed dispersal syndrome. Results: Seeds from wet grasslands lived longer and had consistently higher germination rates than seeds from open savannas. Additionally, fresh seeds dispersed late in the wet season had higher levels of seed dormancy compared to seeds dispersed early in the wet season. Finally, we found that anemochoric seeds had lower levels of dormancy than barochoric seeds. Conclusions: Seed dormancy among Neotropical grasses was higher for seeds of species from dry habitats, dispersed late in the wet season, and with short distance dispersal (barochory). These results suggest that seed dormancy is a key mechanism by which seeds avoid seedling emergence in the dry season, an effect offset by habitat‐specific soil moisture availability. The trade‐off between dormancy and seed dispersal suggests that both strategies are costly and had non‐additive benefits. Abstract : We accessed the seed dormancy of grass species from seasonal savannas and wet grasslands of Brazil. Seed dormancy was higher for seeds of species from dry habitats, dispersed late in the wet season, and with short‐distance dispersal. This results suggest that seed dormancy is a key mechanism to avoid seedling emergence near the dry season and to avoid crowding.